DESCRIPTIVE OF KNOWLEDGE LEVEL ON PARACETAMOL USE AND THE EFFECTIVENESS OF RECOVERY FROM PRIMARY CEPHALGIA AMONG MEDICAL STUDENTS - Alifia, Khalisya; Kosasih, Robert (Journal of Pain, Headache and Vertigo, 2026)
Primary cephalgia is a commonly experienced neurological condition, frequently self-managed by university students using over-the-counter medications such as paracetamol. While accessible and widely used, improper use of paracetamol—due to limited knowledge—can result in suboptimal symptom relief or serious adverse effects such as overdose and hepatotoxicity. This study aims to describe the level of knowledge regarding paracetamol use and its perceived effectiveness in alleviating primary cephalgia symptoms among medical students class of 2022 and 2024 at Tarumanagara University. This descriptive research utilized a cross-sectional design. Data were collected through a structured and validated questionnaire that assessed students’ knowledge about appropriate dosage, indications, side effects, and contraindications of paracetamol. To evaluate effectiveness, participants rated the intensity of their cephalgia before and after paracetamol intake using a standardized pain scale. The results revealed varied levels of knowledge across the respondents. While a considerable proportion of students demonstrated adequate knowledge—especially regarding dosage and indications—knowledge gaps were evident in understanding potential side effects and overdose risks. Furthermore, a statistically significant positive correlation was identified between higher knowledge scores and greater reported reduction in pain severity after paracetamol use. In conclusion, students with a stronger understanding of paracetamol usage experienced more effective relief of primary cephalgia symptoms. These findings underscore the necessity of targeted educational interventions that promote the rational and safe use of over-the-counter analgesics. Enhancing students’ pharmacological literacy is essential to improving therapeutic outcomes and minimizing the risks associated with self-medication practices.